Common wealth : economics for a crowded planet - Sachs, Jeffrey (New York : Penguin Press, 2008)
Assessment of the environmental degradation, rapid population growth, and extreme poverty that threaten global peace and prosperity, with practical solutions based on a new economic paradigm for our crowded planet.
Common challenges, common wealth -- Our crowded planet -- The anthropocene -- Global solutions to climate change -- Securing our water needs -- A home for all species -- Global population dynamics -- Completing the demographic transition -- The strategy of economic development -- Ending poverty traps -- Economic security in a changing world -- Rethinking foreign policy -- Achieving global goals -- The power of one.
Includes bibliographical references (p. [361]-369) and index.
Keywords: Economic policy; Sustainable development